Biochemical and Cuticular Variation in Teak Clone Leaves and Resistance to Teak Defoliator - Jacob, J. Prasanth; Balu, A. (Indian Forester, 2007)
Nine resistant teak clones identified based on a four-year field survey were taken for confirmation of its resistant nature against teak defoliator, Hyblaea puera, by comparing the feeding preference with most susceptible and moderately susceptible teak clones under controlled conditions in a choice and no-choice situation. Three clones showed minimum or negligible feeding damage without significant variation under choice and no-choice situation. The study also demonstrated the physical and chemical variations in resistant and susceptible clone leaves, which may interfere with the feeding behaviour of H. puera. Observed results call for a detailed study on genetic variation in physical and chemical properties in tree clones of economic importance for exploitation to develop resistant strains of trees against key pests through breeding as well as genetic engineering/transformation.